1991
DOI: 10.3354/meps078123
|View full text |Cite
|
Sign up to set email alerts
|

Grazing pressure of the calanoid copepod Temora longicornis on a Phaeocystis dominated spring bloom in a Dutch tidal inlet

Abstract: Between 30 March and 1 1 May 1990, total copepod abundance and the abundance. b~o m a s s and gut fluorescence of Temora longlcornls were determined and related to the abundance and succession of phytoplankton development in a Dutch tidal inlet Gut plgment values were h~g h e s t In females and lowest In young copepodites, but weight-spec~f~c pigment concentrations were about slrnilar Pigment levels measured In the guts were relatively high at the beginning and end of the penod of investigation when diatoms d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 30 publications
(32 reference statements)
4
50
0
Order By: Relevance
“…Based on the spring biomass increase of T. longicornis, Hansen & van Boekel (1991) calculated a required ingestion of 70 to 140 % body weight daily, which is well in agreement with results from laboratory growth experiments (Klein Breteler et al, 1990). In contrast to the results of the experiments in which only algal food was present,…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Based on the spring biomass increase of T. longicornis, Hansen & van Boekel (1991) calculated a required ingestion of 70 to 140 % body weight daily, which is well in agreement with results from laboratory growth experiments (Klein Breteler et al, 1990). In contrast to the results of the experiments in which only algal food was present,…”
Section: Discussionsupporting
confidence: 74%
“…The gut pigment content of males females and smaller copepods, did not resemble the seasonal course of the chlorophyll-a concentration in the water (Figs 3, 4) It was inversely correlated with the dominance of Phaeocystis (Figs 4,5). Calculated ingestion of phytoplankton was negligible during the Phaeocystis bloom and far too low to fulfil Temora's metabolic needs, which w~r~ ~timated from its biomass increase (Hansen & van Boekel, 1991}. It was concluded that Temora had switched to a heterotrophic food source and it has been snggest~d that this could have been a bloom of ciliate.~ present during the Phaeocystis-dominated period of the phytoplankton spring bloom (van Boekel et al, 1992). The hypothesis is put forward that 7", longicornis preferentially feeds on microzooplankton and by this may enhance, rather than depress, Phaeocystis blooms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations